New perspectives on theories linking cognition, emotion, and context: A proposal from the Theory of Analysis of Demand. (19th May 2018) - Petitta, Laura; Ghezzi, Valerio; Jiang, Lixin
Abstract: Both scholars and practitioners acknowledge that the major factors explaining behavior are cognition, emotion, and context. However, existing theories tend to only focus on a combination of two. Furthermore, not all models are rooted in a specific theory of mind. Finally, there is no consistent definition of 'mind.' To address these issues, we review the major models explaining behavior. We then describe the Theory of Analysis of Demand (TAD), an interactionist (individual-context) model of functioning of mind that thoroughly addresses the conjoint interplay of cognition, emotion, and context. A key concept of the TAD is emotional symbolization, the process of relating one's experiences of the external context with an inevitable emotional reaction. By considering an intersection among cognition, emotion, and context, TAD fills the gap in the existing literature and expands our understanding of behavior. Moreover, we describe the TAD intervention methodology, Individual-Setting of intervention-Organization technique, which explores an individual's demand for intervention and the underlying emotion-, cognition-, and context-related categories (i.e., emotional symbolization) that prompt the request. Last, we discuss the potential benefits and boundary conditions of the TAD to integrate existing approaches.